Physicians' experiences of intercultural differences in communication with Ukrainian refugees during the Russian-Ukrainian armed conflict - Jelínková, Marie; Dobiášová, Karolína; Těšinová, Jolana Kopsa; Koščík, Michal (Casopis lekaru ceskych, 2023)
The aim of the study was to identify and explore barriers to communication between refugees from Ukraine and physicians providing health care, the perspective of physicians was embraced. The focus of the work reflects on the arrival of many forced migrants from Ukraine in 2022. Further, it focuses on the pressure that the presence of migrants' places on the Czech healthcare system, especially in doctor-migrant patient communication. The objectives of this study are also motivated by existing international evidence that misunderstandings and poor-quality communication can lead to lower patient satisfaction and adherence, and consequently poorer healthcare outcomes. The research was carried out in the form of qualitative research, 16 in-depth semi-structured interviews were conducted with physicians providing health care to Ukrainian refugees. Informants were selected using a purposive sampling method to obtain as diverse a sample as possible. The resulting data were analysed by applying thematic coding. The results showed that four main areas of intercultural barriers play a key role in the relationship between physicians and Ukrainian patients. These are: (1) language, (2) differences in healthcare systems, (3) different attitudes towards health and illness and (4) prejudice. The major source of misunderstanding was the difference between the Czech and Ukrainian healthcare systems, which leads to a different position of the patient in the healthcare system. The conclusions prove that intercultural barriers play a significant role in the provision of health care to Ukrainian refugees but can be addressed to a large extent. The current situation in Czechia and the increasing diversity in society call for the need to acquire intercultural competencies in undergraduate and continuing medical education. Similarly, the adoption of measures that promote culturally competent health care is needed.
Keywords: jazyk (prostředek komunikace); komunikace; ozbrojené konflikty; Health Services Accessibility; Refugees; Armed Conflicts; dostupnost zdravotnických služeb; Ukraine; language barriers; migrants; Humans; Communication; Language; uprchlíci; different health systems; lékaři; Physicians; cultural barriers; lidé